Respuesta :
To solve by completing square method we proceed as follows:
2x^2+16x=-18
dividing through by 2 we get:
x^2+8x=-9
but
c=(-b/2a)^2
c=(-8/2)=16
hence
x^2+8x+16=-9+16
x^2+8x+16=7
(x+4)(x+4)=7
(x+4)^2=7
thus getting the square root of both sides
x+4=+/-√7
x=-4+/-√7
x=
2x^2+16x=-18
dividing through by 2 we get:
x^2+8x=-9
but
c=(-b/2a)^2
c=(-8/2)=16
hence
x^2+8x+16=-9+16
x^2+8x+16=7
(x+4)(x+4)=7
(x+4)^2=7
thus getting the square root of both sides
x+4=+/-√7
x=-4+/-√7
x=
Answer:
[tex]x = -4 \frac{+}{-} 2\sqrt{5\\}[/tex]
Step-by-step explanation: